Le religioni asiatiche secondo gli adolescenti italiani - Lapis, Giovanni (Annali di Ca’ Foscari: Serie Orientale, 2023)
Research on the cultural influence of Asian religions in Western countries tends to overlook younger actors as receivers and producers of innovation. By applying a theoretical framework that highlights the cultural role of nationalism, neoliberalism and consumerism in shaping religious behaviour, the article analyses, through interviews, the interpretation of Asian religions among a purposive sample of adolescents and put them within the larger context of the physical and mediatic presence of these religions in society. It argues that these adolescents further align themselves with those trends in Italian society which follow the so-called ‘Global Market Regime’. It also provides reflections on the implications of this situation concerning religious and intercultural education.